Relationship between CCL25/CCR9 Levels in Follicular Fluid and High Ovarian Response in Patients with Polycystic Ovary Syndrome - Yongxin Hao; Qianqian Yin; Fangfang Hu; Xiaoyan Liu; Yaru Yang; Fang Sun; Xiaonan Yan (International Journal of Endocrinology)
Objective. Polycystic ovary syndrome (PCOS) is one of the prevalent gynecological endocrine disorders encountered in clinical practice. Women diagnosed with PCOS demonstrate increased ovarian responsiveness, rendering them more prone to ovarian hyperstimulation syndrome (OHSS) during controlled ovarian stimulation (COS) procedures. The current study aimed at investigating whether CCL25/CCR9 plays a role in the pathological process of high ovarian response (HOR) during COS procedures. Design. Single-center retrospective cohort study. Patients. A total of 200 PCOS patients who received a fixed regimen of gonadotropin-releasing hormone (GnRH) antagonist were enrolled in this study. The cohort comprised 118 patients exhibiting HOR and 82 patients demonstrating a normal ovarian response (NOR). Results. The age and body mass index (BMI) variances across the two groups did not differ significantly. Similarly, the two groups observed no statistically significant differences in the baseline levels of luteinizing hormone (LH), progesterone (P), estradiol (E2), basal prolactin (PRL), and testosterone (T). Compared to the NOR group, HOR patients exhibit markedly elevated levels of anti-Müllerian hormone (AMH), antral follicle count (AFC), basal follicle-stimulating hormone (FSH), and HOMA-IR (all p < 0.05). Conversely, no statistically significant differences were observed between the two groups with respect to COS parameters, encompassing initial gonadotropin (Gn) dose, stimulation duration, and total Gn dose. During COS, the number of oocytes with diameter ≥14 mm, the levels of E2 on the HCG day, and the number of retrieved oocytes were significantly higher in the HOR group than in the NOR group (all p<0.001). Additionally, the levels of CCL25/CCR9, matrix metalloproteinases (MMPs), tissue inhibitor of metalloproteinases (TIMPs), TNF-α, and IL-6 were significantly higher in the FF of the HOR group than in the NOR group (all p<0. 001), while the variance in IL-1β levels between the two cohorts did not reach statistical significance. The relevance analysis results indicated that the levels of CCL25/CCR9 in the FF of the HOR group are positively correlated with the number of retrieved oocytes and oocytes with diameters ≥14 mm during COS, AMH levels, and AFC. Concurrently, the CCL25 levels in the FF of the HOR group were positively correlated with HOMA-IR. Multivariable linear regression analysis revealed that the elevated AFC and HOMA-IR independently increase the CCL25 levels. Conclusion. The CCL25/CCR9 levels in FF are positively correlated with the clinical indicators of HOR, suggesting that CCL25/CCR9 may play a role in the pathogenesis of HOR in patients with PCOS.